A Quantitative Examination of School Leadership and Response to Intervention. Issue 2 (17th May 2016) - Maier, Michael P.; Pate, James L.; Gibson, Nicole M.; Hilgert, Larry; Hull, Karla; Campbell, Patti C.
Abstract : This study sought to provide educational researchers, policy‐makers, and professionals with quantitative data on the status of RTI implementation, as well as on which leadership behaviors have been associated with successful implementation. School psychologists and other RTI professionals rated their schools on RTI implementation using the RTI Essential Components Integrity Rubric and rated their school principals on leadership style using the Multifactor Leadership Questionnaire 5X. Descriptive data indicate that while schools have made progress, they have fallen far short of having fully implemented the RTI model. Multiple regression analysis identified transformational leadership as the predictive factor for RTI implementation, highlighting the importance of effective school leadership for this model.